lassification Study of Solid Medical Waste in Heet General Hospital - Ziad Kamil Mohsen; Dhafer F. Alrawi (Indian Journal of Forensic Medicine & Toxicology, 2022)
Is rated about (10-25 %) Of these wastes as hazardous and can affect the public health environment and pollution in particular, the medical waste m n this hospital if it is not handled properly can cause health problems for health workers in the hospital and for the patients and the community. Medical waste consists of hazardous waste and non - hazardous wastes include waste and hazardous waste infectious , disease, drugs , sharp tools, chemicals, toxic waste genetic and radioactive either non - hazardous waste fats included garbage and general daily waste of residues of food , materials , office and other.